Usury and Macroeconomic (In)stability : A Comparative Study of Norway and United Arab Emirates - Ma, Wei; Máslo, Lukáš Augustin, 1985-; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
Since the outbreak of the financial crisis in 2008, in some Islamic countries where usury is illegal, they are not only unaffected by the crisis, but also can make surpluses.So from this perspective author gives the hypothesis that do the usury-free economies cope with financial crises better than usury-based economies? The analysis specifically focus on United Arab Emirates(Islamic economy) and Norway, and the data take from 2004-2014. The theoretical and practical studies are conducted in this thesis. First of all, author is inspired by Brian M. McCall(2008) and Hyman Minsky(1978), start from basic information about usury, Islamic, economy and macro-instability, which Hyman Minsky’s financial instability hypothesis is used. Next author focus on the measurement of stability of UAE and Norway’s economy, the machine learning decision tree algorithm (XGBoost) and principal component analysis (PCA) is used to verify the matching degree between the selected input variables and the output variables in the period of fluctuation and stability of the two countries and drive the conclusion that that the usury-free economy can cope the financial crisis better.
Vedoucí práce: Lukáš Augustin Máslo
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses